Narrative Review: Analisis Fitokimia Dan Manfaat Ekstrak Ketepeng Cina (Cassia alata L.) Sebagai Antijamur - Udin, Baha; Ismiyati, Renditya; Ismiyati, Renditya; Kholifah, Eva; Endah, Endah; Endah, Endah (Jurnal Farmasi Udayana; Vol. 12, No 1, Tahun 2023DO - 10.24843/JFU.2023.v12.i01.p08, 2023)
Indonesia is known to have various types of plants that can be used in medicine, one of which is Cassia alata . Cassia alata is a plant that has many properties so it can be used as herbal medicine or traditional medicine. One of the properties of the Cassia alata plant that has been widely studied is as an antifungal. Every part of the Cassia alata plant has secondary metabolites. Cassia alata leaves contain secondary metabolites of alkaloids, steroids, phenols, glycosides, terpenoids and flavonoids. Cassia alata flowers contain flavonoids, tannins and phenolic compounds and saponins. Cassia alata level contains alkaloids, flavonoids, glycosides, phytosterols, quinones, tannins and terpenoids. Compounds that have a role or antifungal activity in Cassia alata are phenolics, tannins, flavonoids, saponins, triterpenoids, steroids, and alkaloids.